Characterization of oil palm empty fruit bunch fibres- microcrystalline cellulose for potential high mechanical strength paper - Ismail, Faris Syahiran (2019)
The abundance of biomass generated from oil palm industry can be utilized by producing value added products such as high durability paper. Therefore, this study aimed to determine the effects of oil palm empty fruit bunch (OPEFB) pulp and paper properties after beating and adding microcrystalline cellulose (MCC) during the papermaking process. The pulps were produced using Kraft pulping condition with the incorporation of 0%, 3%, 6% and 9% of MCC during papermaking process. The pulps were also beaten at 500 and 1,000 revs of beating level. TAPPI Standard Method was used for the papermaking. Pulp characterization involved pulp freeness, pulp viscosity, pulp drainage and morphological observation. Paper testing included physical, optical, mechanical and thermal properties. Chemical composition of EFB fibre showed an amount of 43.66% and 25.74% of alpha cellulose and of lignin respectively which were suitable for pulping process. The removal of lignin about 82.71% and increase in percentage of alpha cellulose after the pulping process indicated that the pulps can be used to produce high strength paper. Increased fibrillation caused by beating resulted in lower freeness value of 1,000 beaten pulps compared to other samples. Micrograph observations of the paper showed that the paper became more flatten with the introduction of beating and consequently, decreased the thickness of paper. Smoothness of the paper increased with higher beating revolution and higher concentration of MCC, but porosity worsened. The result indicated that addition of MCC into the beaten and unbeaten pulps resulted in positive effect to the mechanical strength of the paper. Tensile index and tear index of unbeaten pulps showed increment by 71.4% and 24.5%, respectively with the addition of 9% MCC concentration, while 6% MCC to 500 revolutions beaten pulps increased freeness value, tear strength, burst strength, folding endurance and brightness by 1.15%, 39.07%, 18.54%, 0.06% and 4.74%, respectively. Optical properties of the paper showed that unbeaten pulp decreased with the addition of MCC in terms of brightness, whereas the brightness of the beaten pulps increased with increasing concentration of MCC. Thermal analysis showed that MP0a (EPB pulp) had the highest thermal degradation compared to other samples. Addition of MCC resulted in negative effect to thermal stability as it decreased the thermal stability of the unbeaten and beaten pulps. In conclusion, the study discovered that the less than 6% of MCC improved the properties of the 500 revolutions beaten pulps in terms of mechanical strength, while overdose of MCC addition and high beating revolution of EFB fibres degraded all major properties of the paper.